Síntese, caracterização e aplicação de estruturas compostas por óxido de grafeno na adsorção de antibióticos em água residuária sintética - Gomes, Bruna Ferreira (2024)
The occurrence of emerging contaminants such as antibiotic drugs has shown the need for the development of advanced technologies for the treatment of wastewater and supply. Therefore, this work aimed to investigate the removal of antibiotics in synthetic wastewater through adsorption using graphene oxide structures. To this end, structures based on graphene oxide (OGD), graphene oxide-bismutite (OGD-Bi) and reduced graphene oxide (OGD-RED) were synthesized and characterized. Subsequently, adsorption tests were carried out using the batch method, in which the antibiotics ciprofloxacin (CIP), sulfamethoxazole, tetracycline and chloramphenicol were tested in synthetic wastewater at pHs 5 and 8. CIP was selected to evaluate the kinetics and balance of the adsorption process using graphite precursor (GRF) and other adsorbents based on graphene oxide. The contact time for equilibrium to be reached was 240 min, with greater efficiency for OGD (98.8% at pH 5 and 82% at pH 8). For this antibiotic, the kinetics followed pseudo-second order behavior with data adaptation by the Sips isotherm, suggesting the chemisorption mechanism in the OGD, OGD-Bi and OGD-RED adsorbents. For the GRF, there was a correlation with the pseudo-first order model and the Freundlich isotherm, indicating physisorption. The results of this research demonstrated that OGD-based materials have potential in removing antibiotics, with emphasis on CIP, through the adsorption technique.